The Sea House - Freud, Esther (London Penguin Books, 2004)
The Sea House is the story of the village of Steerborough and the marshes and the sea beyond. It is the story of one generation living in the footprints of another; of a landscape shaped by lives, and lives shaped by landscape. With characteristic skill and a new depth and range, Esther Freud explores the twisting paths that people take -- and the places where those paths meet.
English Fiction.
Keywords: Married people -- Women biographers -- Young women